2005
DOI: 10.1111/j.1476-5810.2005.00070.x
|View full text |Cite
|
Sign up to set email alerts
|

Carboplatin and piroxicam therapy in 31 dogs with transitional cell carcinoma of the urinary bladder

Abstract: Invasive transitional cell carcinoma (TCC) of the urinary bladder responds poorly to medical therapy. Combining platinum chemotherapy with a cyclooxygenase (cox) inhibitor has shown promise against canine TCC, where the disease closely mimics the human condition. A phase II clinical trial of carboplatin combined with the cox inhibitor, piroxicam, was performed in 31 dogs with naturally occurring, histopathologically confirmed, measurable TCC. Complete tumour staging was performed before and at 6-week intervals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
101
4
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(111 citation statements)
references
References 21 publications
4
101
4
2
Order By: Relevance
“…Most patients that experienced high‐grade neutropenia were asymptomatic and recovered without intervention other than prophylactic antibiotics. Gastrointestinal toxicosis was far less common in the carboplatin‐treated dogs (26%) in this study compared to a previous study where 74% of dogs with TCC receiving the combination of carboplatin and piroxicam developed gastrointestinal toxicosis 15. Similarly, the hospitalization rate in this study was much lower than previously reported.…”
Section: Discussioncontrasting
confidence: 68%
See 3 more Smart Citations
“…Most patients that experienced high‐grade neutropenia were asymptomatic and recovered without intervention other than prophylactic antibiotics. Gastrointestinal toxicosis was far less common in the carboplatin‐treated dogs (26%) in this study compared to a previous study where 74% of dogs with TCC receiving the combination of carboplatin and piroxicam developed gastrointestinal toxicosis 15. Similarly, the hospitalization rate in this study was much lower than previously reported.…”
Section: Discussioncontrasting
confidence: 68%
“…Responses to carboplatin and piroxicam have also been noted in dogs that have not responded to other therapies, and the MST in these dogs was 161 days 15. The overall response rate was 38% in that report; however, gastrointestinal toxicosis was high (noted in 74% of dogs), and 25.8% was hospitalized 15. A PFI of 41 days has been reported in dogs treated with carboplatin alone 16.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…In this dog, toceranib was used as first line due to ease of administration and tolerability, which was important to the owner. Conventional chemotherapy with platinum agents was chosen based on reported efficacy in various types of carcinomas (Boria et al, 2005;Dominguez et al, 2009) as well as metronomic chemotherapy, which has been previously administered to dogs with different solid tumours (Burton et al, 2011;Spugnini et al, 2014), although we were able to achieve only short-lived responses. The dose of bisphosphonates was chosen based on a recent study where dogs treated at 2 mg/kg were found to have lower levels of N-telopeptide in the urine, suggesting a reduction in focal osteolysis, earlier than dogs receiving a dose of 1 mg/kg, although the difference was not statistically significant (Fan et al, 2007).…”
Section: Discussionmentioning
confidence: 99%